(untitled) (Swiss Medical Weekly, 2019)
BACKGROUND Systematic work-up of patients with myocardial infarction and non-obstructive coronary artery disease (MINOCA) using cardiac magnetic resonance imaging (CMR) led to a more than six-fold increase in the detection rate of myocarditis. In this study, we expanded on our prior two-year analysis by including preceding and subsequent years. METHODS We performed a retrospective chart review of patients with angina-like symptoms and elevated high-sensitivity troponin T (TnT-hs ≥14 ng/l) but without significant coronary artery disease, from 2011 to 2017. Patients underwent CMR to test for myocarditis. From 2011 to 2015, only patients with elevated TnT-hs, no significant coronary artery disease and moderate to high clinical likelihood of suffering from myocarditis, underwent CMR. In 2016 and 2017, CMR images were obtained from all patients with MINOCA, independent of the clinical likelihood that patients were suffering from myocarditis. RESULTS A total of 556 patients who underwent CMR (70.5% male, 57 ± 17 years, with an average left ventricular ejection fraction of 51 ± 15%) qualified for inclusion in this study’s analysis. From 2011 to 2015, 240 CMR examinations were performed, with the number increasing to 316 between 2016 and 2017. In total, myocarditis was diagnosed in 76 out of the 556 patients (13.7%). Between 2011 and 2015, the detection rate of myocarditis was 12.7 per 100,000 hospitalisations and increased 4.9-fold (p <0.0001), to 62.5 per 100,000 hospitalisations, between 2016 and 2017. CONCLUSION A novel diagnostic algorithm led to an average 4.9-fold increase in the rate of myocarditis detection in our hospital over the two subsequent years. This highlights that myocarditis continues to be underdiagnosed when CMR is not systematically used in patients with MINOCA.